Screening and optimization of arsenic degrading bacteria and their potential role in heavy metal bioremediation (Bioscience Journal, 2019)
Industrialization has added extremely toxic metalloid arsenic into the environment which at high concentration severely threatens the biota. Naturally, some microbes possess the ability to bio-accumulate metals and also to transform arsenite (As III) a toxic form to a non-toxic arsenate As V. The present study aimed to isolate arsenic resistant bacterias from the arsenic contaminated soil and water. Among eleven bacterial isolates, three FAs 1, 4 and 9 exhibited tolerance against sodium arsenite at 100mM concentration by achieving growth of 7.48×109,1.57×109 and 2.23×109 C.F.U./ml, respectively. Optimization at different conditions such as temperature, pH and arsenic concentration revealed high arsenic tolerance from isolate FAs 4 (5.33×108) at 37°C and FAs 1 (4.43×108 C.F.U./ml) at pH 7. Arsenic resistance at optimum conditions for the bacterial strains FAs 1, FAs 4 and FAs 9 showed maximum growth at 80mM concentration of arsenite. These bacterial isolates did not show redox ability to oxidize arsenite As III to arsenate As V. However bacterial isolates FAs 1, FAs 4 and FAs 9 were able to accumulate arsenic 39.16, 148 and 125 µg/L on the 4th, 3rd and 5th day of incubation, respectively. The isolates FAs 1, FAs 4 and FAs 9 were identified as Gram negative non endospore forming rods. In future, these novel isolates possess a great potential in biotechnology field, as bioremediation of arsenic contaminated soil and water can be done by employing arsenic accumulating bacteria which is an eco-friendly and cost effective method.